Το επιμορφωτικό ντοκιμαντέρ «Η διαδρομή του βιβλίου: από το συγγραφέα στον αναγνώστη» - Κατιδιώτη, Ιωάννα; Μπαμπουκλή, Ιωάννα; Σοφός , Αλιβίζος (Λοΐζος) (Open Journal of Animation, Film and Interactive Media in Education and Culture [AFIMinEC], 2022)
The educational documentary “The journey of books: from the writer to the reader” aims to inform the viewers about the creation of a book and the different stages that includes, starting from writing a book, up until the copies of the book are placed on the selves of bookstores. The journey begins from the writer, continues in the publishing house, followed by production of the book (printing and binding), promotion of the book by the publishing house and finally, the bookstore, where the reader can purchase the book. Simultaneously, the documentary offers historic facts about the creation of books.